Long-term follow-up in common variable immunodeficiency: the pediatric-onset and adult-onset landscape - Carrabba, Maria; Salvi, Marco; Baselli, Lucia Augusta; Serafino, Serena; Zarantonello, Marina; Trombetta, Elena; Pietrogrande, Maria Cristina; Fabio, Giovanna; Dellepiane, Rosa Maria (Frontiers in Pediatrics, 2023)
Introduction The primary aim of this study is to investigate the evolution of the clinical and laboratory characteristics during the time in a longitudinal cohort of pediatric-onset and adult-onset Common Variable Immunodeficiency (CVID) patients in order to identify early predictive features of the disease and immune dysregulation complications. Methods This is a retrospective-prospective monocentric longitudinal study spanning from 1984 to the end of 2021. The data of pediatric-onset vs. adult-onset patients have been compared for immunological features and for infectious and non-infectious complications assessed at diagnosis and follow-up. Results Seventy-three CVID patients have been enrolled, with a mean of 10.0 years (SD ± 8.17) of prospective follow-up. At diagnosis, infections were observed in 89.0% of patients and immune dysregulation in 42.5% of patients. At diagnosis, 38.6% of pediatric-onset and 20.7% of adult-onset patients presented with only infections. Polyclonal lymphoid proliferation (62.1%) and autoimmunity (51.7%) were more prevalent in the adult-onset than in the pediatric-onset group (polyclonal lymphoid proliferation 52.3% and autoimmunity 31.8%, respectively). Enteropathy was present in 9.1% of pediatric-onset and 17.2% of adult-onset patients. The prevalence of polyclonal lymphoid proliferation increased during follow-up more in pediatric-onset patients (diagnosis 52.3%—follow-up 72.7%) than in adult-onset patients (diagnosis 62.1%—follow-up 72.7%). The cumulative risk to develop immune dysregulation increases according to the time of disease and the time of diagnostic delay. At the same age, pediatric-onset patients have roughly double the risk of having a complication due to immune dysregulation than adult-onset patients, and it increases with diagnostic delay. The analysis of lymphocyte subsets in the pediatric-onset group showed that CD21 low B cells at diagnosis may be a reliable prognostic marker for the development of immune dysregulation during follow-up, as the ROC curve analysis showed (AUC = 0.796). In the adult-onset group, the percentage of transitional B cells measured at diagnosis showed a significant accuracy (ROC AUC = 0.625) in identifying patients at risk of developing immune dysregulation. Discussion The longitudinal evaluation of lymphocyte subsets combined with clinical phenotype can improve the prediction of lymphoid proliferation and allow experts to achieve early detection and better management of such complex disorder.